Pengaruh E-LKPD berbasis Liveworksheet untuk Meningkatkan Hasil Belajar pada Materi Kekayaan Budaya Indonesia SD Negeri 3 Wonorejo - Pratiwi, Eriska Diah; Putri, Dya Ayu Agustiana; Oktaviarini, Nourma (Jurnal Simki Postgraduate, 2025)
Learning media is an important tool for improving learning outcomes. Learning outcomes emerge when students are motivated in learning. The aim of the research is to determine the effect of interactive learning media on the learning outcomes of grade 4 students at SD 3 Wonorejo. This research is quantitative with an experimental type. The sampling technique used saturated sampling with 30 respondents. Data collection techniques use learning outcomes tests. The data analysis technique uses the t test (Independent Samples T-Test) in Jamovi 2.3.28. The results of the post-test t test showed that the p-value was <0.001, then the p-value was <0.05 and H0 was rejected and Ha was accepted, which means that the Liveworksheet-based E-LKPD had a positive influence on student learning outcomes on Indonesian natural wealth material. Based on the results of the hypothesis, it was found that there was a significant effect of Liveworkshet-based E-LKPD on improving the learning outcomes of class IV students at SD Negeri 3 Wonorejo.